What Money Can Buy: How Market Exchange Promotes Values - Roberto A. Weber; Sili Zhang (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study consumers' concerns for the ideological values of their market counterparts and the implications of such concerns for the public promotion of values. Using a survey and online and laboratory experiments, we find that consumers are willing to pay premiums to exchange with counterparts who demonstrate support for their values. When sellers anticipate the possibility of market exchange, they exhibit public support for consumers' values. Our findings challenge notions that market exchange is impersonal, suggest that public value positions can provide a dimension of firm differentiation, and provide evidence that market exchange can influence public support for ideological values.
Keywords: A13; C90; D12; D22; D91; 330; market exchange; ideology; values; experiment